1990
DOI: 10.3109/00365529008997607
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Non-Epithelial Tumours of the Thoracic Oesophagus and Cardia in a 25-Year Surgical Material

Abstract: During 25 years, 708 patients with primary malignant tumours of the thoracic oesophagus (n = 376) or cardia (n = 332) were referred to our department. Two hundred and forty-nine patients had squamous cell carcinoma and 425 adenocarcinoma. The other 34 tumours, which were primarily classified as undifferentiated carcinoma, malignant carcinoid or non-epithelial, were re-evaluated by means of a second microscopic histologic examination and immunohistologic investigation. This showed primary malignant non-epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It was fi rst reported in 1983 [3], and since then only seven cases, including our case, have been reported in the international literature (seven men; age range, 46-78 years; mean age, 60 years) [16][17][18][19][20]. Mean diameter of the tumor was 9.0 cm ( Table 1).…”
Section: Discussionmentioning
confidence: 75%
“…It was fi rst reported in 1983 [3], and since then only seven cases, including our case, have been reported in the international literature (seven men; age range, 46-78 years; mean age, 60 years) [16][17][18][19][20]. Mean diameter of the tumor was 9.0 cm ( Table 1).…”
Section: Discussionmentioning
confidence: 75%
“…Of these, 13 were women and 11 were polypoid, supporting the observation by Rainer and Brus that women with polypoid tumors may have a better prognosis [15,21]. Further search of the literature uncovered an additional 37 cases, 29 of which were reported in a 1980 review of the Japanese experience that noted a 22% 5-year survival, including four patients alive and well 9-13 years after resection [lo, [16][17][18][19]. Radical esophagectomy has been the treatment of choice, but Choh et al note that simple resection of well-localized lesions can be as effective as radical excision [ 151.…”
mentioning
confidence: 63%
“…The combination of an extended radical surgery and DAV (DTIC, ACNU, VCR) therapy has been reported to be associated with a more favorable prognosis than in past reports of PMME [10,22,23]. In some reports, combination therapy included platinum analogues and tamoxifen [22].…”
Section: Discussionmentioning
confidence: 97%
“…Futhermore, Ohashi et al suggested that an increased number of melanocytes, which is frequently observed in areas with a hyperplastic epithelium and chronic esophagitis, may play an important role as a precursor lesion for malignant melanoma of the esophagus [7]. PMME accounts for 0.1%-0.2% of all the esophageal tumors and about 250 cases have so far been described in the literature [8][9][10]. PMME shows a relatively uniform clinical pattern: patients complain of dysphagia (79.8%), weight loss (37.5%), and substernal or epigastric pain (33.1%).…”
Section: Discussionmentioning
confidence: 99%